The Karakteristik Anemia pada Pasien Hemodialisis Rutin di RSUD Provinsi NTB : Karakteristik Anemia pada Pasien Hemodialisis Rutin di RSUD Provinsi NTB - Yunandari Ni Putu; Ima Arum Lestarini; I Gede Yasa Asmara3 (Lombok Medical Journal, 2024)
Abstract Background: The most common complication in End Stage Renal Disease (ESRD) undergoing hemodialysis (HD) is anemia. Anemia increases mortality and morbidity. This study aims to determine the characteristics of anemia in ESRD patients undergoing HD. Method: This research is a cross-sectional observational analytical study and the sample is ESRD patients undergoing HD at the NTB Provincial Regional Hospital in 2021, taken consecutively. Data came from medical records and were analyzed univariately and bivariately using the Chi-Square test. Result: The prevalence of anemia in HD patients was 66.3%. Characteristics of ESRD patients undergoing HD include female gender (52.7%), middle age (61.4%), anemia (71.9%), mild anemia (72.7%), normocytic morphology (77.3%), normal serum iron (79.1%), normal TIBC (99.1%), and normal ferritin (82.7%), received iron therapy (29.1%), received erythropoietin (EPO) (86.4%), and had a blood transfusion (15.5%). In bivariate analysis, it was found that there was no significant relationship between the incidence of anemia and gender (p=0.084) and age (p=0.980). There was no relationship between the degree of anemia and iron therapy (p=0.672). There was a significant relationship between the degree of anemia with EPO therapy (p<0.001), and the degree of anemia with blood transfusion (p<0.001). Conclusion: The characteristics of anemia in regular HD patients are dominated by men, middle-aged adults, mild anemia, normocytic morphology, normal iron status, and the therapy given includes serum iron, EPO, and blood transfusions. Keywords: anemia, hemodialysis, characteristics